Investigating Interdisciplinary Collaboration Theory and Practice across Disciplines - Frickel, Scott; Albert, Mathieu; Prainsack, Barbara (Rutgers University Press, 2016)
Interdisciplinarity has become a buzzword in academia, as research universities funnel their financial resources toward collaborations between faculty in different disciplines. In theory, interdisciplinary collaboration breaks down artificial divisions between different departments, allowing more innovative and sophisticated research to flourish. But does it actually work this way in practice? Investigating Interdisciplinary Collaboration puts the common beliefs about such research to the test, using empirical data gathered by scholars from the United States, Canada, and Great Britain. The book's contributors critically interrogate the assumptions underlying the fervor for interdisciplinarity. Their attentive scholarship reveals how, for all its potential benefits, interdisciplinary collaboration is neither immune to academia's status hierarchies, nor a simple antidote to the alleged shortcomings of disciplinary study.